Marketing Strategy Analysis To Increase Sales In The Emping Melinjo Selayar Business - Alief Ali Akbar, Nur; Rizal S, Muh; Seppa, Yusi Irensi; Rivai, Andi Muhammad; Wafiqah Wardah, Siti Syarifah (Jurnal Administrasi Bisnis, 2025)
Analysis of marketing strategies to increase sales in the emping melinjo Selayar business. Thesis of the Business Administration Study Program, AdministrationScience Major, Faculty of Social Sciences and Law, Makassar State University. Supervised by Muh. Rizal S. and Yusi Irensi Seppa. This study aims to identify andanalyze marketing strategies to increase sales of Selayar's emping melinjo business. To achieve this goal, this study used a qualitative approach, this study took 6 (six) respondents, consisting of business actors and business employees. Data collection procedures used were in-depth interviews and documentation. The interview technique was carried out in a structured manner using interviewguidelines. The results of this study indicate that emping melinjo Selayar has not implemented a good and effective marketing strategy according to the theory usedby researchers. In implementing the marketing strategy, Emping melinjo Selayar has not carried out the marketing mix, namely product research, price, place, andpromotion properly in determining a marketing strategy.